The eye of heaven [compact disc, unabridged] - Cussler, Clive; Blake, Russell (Cussler, Clive. Fargo adventures., 2014)
Baffin Island: Husband-and-wife team Sami and Remi Fargo are on a climate-control expedition in the Arctic, when to their astonishment they discover a Viking ship in the ice, perfectly preserved, and filled with pre-Columbian artifacts from Mexico. Soon the Fargos find themselves on the run through jungles, away from those with a personal motivation for stopping them. At the end of the road will be the solution to a thousand-year-old mystery, or death.